Age-related variability in buccal dental-microwear in Middle and Upper Pleistocene human populations - Pérez, Beatriz Pinilla; Romero, Alejandro; Pérez-Pérez, Alejandro (Anthropological Review, 2011)
Infants are thought to present a different buccal microwear pattern than adults and these, therefore, are generally analyzed separately. However, El-Zaatari & Hublin [2009] showed that occlusal texture in Neandertal and modern human juvenile populations did not differ from their elders. The microwear patterns of a sample of 193 teeth, corresponding to 61 individuals of Homo heidelbergensis, H. neanderthalensis and anatomically modern humans (AMH), were analyzed revealing that AMH infants up to 14 years old differ from older individuals in having fewer scratch densities, whereas the Neandertals have a much more variable microwear pattern. Age-at-death and dental age since emergence showed similar though somewhat diverging results, especially in the infant and subadult samples. Differences observed between the Neandertals and modern humans could be reflecting differential wearing patterns or distinct enamel structure and resistance to hard food items consumption. Interpopulation differences in striation densities were not apparent in either subadult or adult individuals, only adult Neandertals (26-45 yrs. old) showed fewer striations than the younger age groups. The AMH sample revealed a gradual cumulative pattern of striation density with age, suggestive of a non-abrupt change in diet.